Rencontres interculturelles à l’hôpital: la consultation médicale avec interprète - Traverso, Véronique (My University, 2002)
This paper presents a current research on intercutural encounters in a hospital service. In the first part of the paper, the different forms that these encounters may take are briefly described and characterized by their main features. The second part of the paper is devoted to those encounters when they take place with a linguistic mediator present. The analysis is a first attempt to grasp the specificities of the communication in this situation, and to cast light on the difficulties raised by this form of three-participant consultation.